Pembelajaran IPS Sekolah Dasar Berbasis Model Pendidikan Karakter - Silvina Noviyanti; Winarni Yulianti; Shella Salsabilla; Haziratul Qudsya (Universitas Batanghari Jambi, 2022)
Social studies learning is an effort to apply social science to understand events and symptoms as well as social problems that occur in real life in people's lives so that they become human beings who are sensitive to the environment. Character education seeks to form, realize and instill personality attitudes of noble character and can have positive attitudes. with high humanity in order to build a strong nation. With social studies learning that examines social life, it is necessary to instill character education that needs to be implemented in learning activities.